Relationship between Exposure to Solid Waste and Dengue Incidence in Communities Surrounding Bakung Landfill Bandar Lampung - Rosmawati, Dwi; Asrowi, Ridho Hanan; Qohar, Abdul; Windari, Fitri (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Abstract Background: Dengue Hemorrhagic Fever (DHF) is a significant public health issue in Indonesia, including Bandar Lampung City. Environmental factors, such as poorly managed landfills, are suspected to contribute to the increase in dengue cases by creating conditions supporting the breeding of Aedes aegypti mosquitoes, particularly through stagnant water formed among unmanaged waste piles. The aim of this study was to analyze the relationship between exposure to solid waste (household waste, non-hazardous industrial waste, and construction waste) around the Bakung landfill and the incidence of dengue fever in the surrounding community. Method: Cross-sectional design was conducted in February 2024 in 200 households within a 500-meter radius of the Bakung landfill, selected through purposive sampling. Data were collected through structured questionnaires, interviews, and environmental condition observations. Statistical analysis used chi-square tests and logistic regression to determine relationships and main risk factors. Result: research results show that there was a significant relationship between solid waste exposure and the incidence of dengue fever (p=0.019), with communities exposed to solid waste (household waste, non-hazardous industrial waste, and construction waste) having a 3 times greater risk of contracting dengue fever compared to those not exposed (OR=3.01; p=0.013). In addition, the habit of maintaining environmental cleanliness was also significantly associated with the incidence of dengue fever (p=0.027). The community with good cleanliness habits has a lower risk of contracting dengue fever (OR = 0.43; p = 0.029). Conclusion: This study emphasizes that poor waste management and low environmental hygiene increase DHF cases. Therefore, efforts to improve waste management in Bakung landfill, community education related to sanitation, and government intervention in disease vector control are needed to reduce the incidence of DHF in the area.